Determining satisfaction of international tourist: A different approach. (September 2019) - Carlos Martin, Juan; Saayman, Melville; du Plessis, Engelina
Abstract: This paper contributes to the discourse on how to determine tourist satisfaction. The aim therefore is to analyze to what extent international tourists visiting South Africa are satisfied by using fuzzy numbers. The measurement of satisfaction with tourist destinations (DSAT) is based on a fuzzy multi-criteria decision-making (F-MCDM) model that evaluates DSAT according to a number of different segments based on gender, age, and mother tongue. We find empirical evidence for DSAT differences between the segments considered in the analysis. Results show that females are more satisfied than males; tourists between 56 and 65 years old are the most satisfied, while millennials younger than 35 are the least satisfied; English mother-tongue speakers are more satisfied than other tourists. Our findings have clear implications for DMOs' managers regarding the design of marketing campaigns for South African destinations, especially for those segments analyzed in the study. Proposals for future research will also be outlined.